Shifting the dimensionality of language: evidence from bilingual Bajau Sama Kota Belud in Malaysia - Renddan, Berawati; Abdul Aziz, Adi Yasran; Dani, Noor Aina (Australian International Academic Centre, 2020)
The language shift phenomenon in the Bajau Sama Kota Belud in Sabah is definite. The researchers surveyed the phenomenon in Kampung Taun Gusi 1, Kota Belud, Sabah. Based on the age cross-sectional method, 300 participants of 20-29 years (G20s), 30-39 years (G30s), 40-49 years (G40s), and 50-59 years (G50s) respectively were selected by stratified sampling. The objective of this study is to formulate the dimensionality of language shift. The researchers found that speakers shifted from using the mother tongue to the Malay language after entering school. The Bajau Sama language spoken as the mother tongue has declined from one generation to another. For a better understanding of the Bajau Sama lexical, G20s meet Fishman's (1991) implication scale negatively. The group achievement of nouns has decreased to 26.9%, verbs (33.9%), and adjectives (32%). Meanwhile, the attitude overtness towards the Bajau Sama language is most evident among G50s with a statistical min of 83.00, declining by 48.20 in G30s and 41.80 in G40s, which eventually and significantly decreased by 23.20 in G20s. In the family domain, G20s prefer using the Malay language over Bajau Sama. In the neighbourhood domain, G20s and G30s use the Malay language frequently. All the groups choose to speak the Malay language in the shop outlet domain. This study's implications demonstrate G20s and G30s have shifted to use the Malay language in family and neighbourhood domains. This shifting justifies the low vocabulary knowledge in Bajau Sama compared to G40s and G50s. Overall, the language shift from the mother tongue to the Malay language in the Bajau Sama Kota Belud community occurred due to bilingualism, the level of status, and unequal power between the two languages, the impact of political, economic, and social situations on one language group. In conclusion, we suggested that the Bajau Sama standard language curriculum be introduced in primary schools to sustain its vitality as a revitalization program.